Kenya : Do Infants Benefit When Older Siblings are Dewormed? - World Bank (Washington, DC, 2015)
Early childhood is a crucial window of opportunity for improving lives. The challenge for policymakers and development experts knows which programs give children’s development the best boost and how to implement them. The World Bank is committed to helping governments understand whether programs to improve lives are succeeding. Rigorous impact evaluations are often carried out to provide the evidence of impact. In Kenya, a World Bank researcher went back after a decade to measure the impact of a deworming campaign on young children whose older siblings and neighbors had received the deworming medication. The evaluation indicates that having fewer worms in their communities gave these younger children a boost, most likely because they faced lower risk of infection during a vital period of development. The results are a reminder of the importance of following up on development programs to measure long-term impacts that can show lasting improvements in the lives of millions. Currently, deworming in Kenya has been scaled up nationwide, giving primary school age children better health and, as this evaluation shows, the chance for cognitive improvement for the youngest family members too.